The effect of stock liquidity on cash holdings: The repurchase motive - Nyborg, Kjell G.; Wang, Zexi (Journal of Financial Economics, 2021)
Enhanced stock liquidity increases a firm’s propensity to hold cash. This is surprising given the view that improved stock liquidity reduces financial constraints. We propose that firms have a repurchase motive for holding cash. Higher stock liquidity strengthens this incentive. Consistent with this, firms with more liquid stock increase cash holdings relatively more when restrictions to repurchases are eased. The effect of stock liquidity on cash holdings is not influenced by access to credit markets. Our findings suggest that the repurchase motive dominates the real investments motive with respect to the effect of stock liquidity on cash holdings.